Safety Assessment of an Oral Therapeutic Dose of Firocoxib on Healthy Horses - Araújo, Renatha A. [UNESP]; Sales, Nathali A. A. [UNESP]; Basile, Roberta C. [UNESP]; Feringer-Junior, Walter H.; Apparício, Maricy [UNESP]; Ferraz, Guilherme C. [UNESP]; Queiroz-Neto, Antonio [UNESP] (MDPI, 2023)
Firocoxib is a non-steroidal anti-inflammatory drug specifically formulated for veterinary medicine and selectively acts on inhibiting the cyclooxygenase 2 enzyme (COX-2). This study evaluated the possible adverse effects of administering oral therapeutic firocoxib on gastric mucosa, hematological parameters, coagulation cascade, and hepatic and renal biochemistry in healthy horses. Nine clinically healthy Arabian horses, approximately 9 years old, received 0.1 mg/kg of oral firocoxib for 14 days. The gastroscopic examination was conducted 1 day before starting treatment (D0) and two days after the last blood collection (D23). Venous blood samples were obtained for laboratory tests on day 1, immediately prior to the initiation of treatment (D1), after 7 and 14 days of treatment (D7 and D14), and 7 days after the conclusion of treatment (D21. No changes were found in the gastroscopic and hematological tests. Coagulation and serum biochemistry levels remain between these species’ average values. However, the increased activated partial thromboplastin time (aPTT) and prothrombin time (PT) indicate reduced blood coagulation capacity, which contradicts the expected effect of treatment with selective COX-2 inhibitors, as these drugs theoretically promote coagulation. Administering firocoxib to horses is safe as it does not cause significant adverse reactions. Therefore, it is a suitable option for managing inflammatory conditions in these animals with attention to an unexpected adverse anti-coagulopathy effect, and further study is warranted.
Keywords: coagulation; drug safety; firocoxib; gastroscopy; hematology; selective COX-2 inhibitor